Feeling like a kid : childhood and children's literature - Griswold, Jerome; Johns Hopkins University (Baltimore : Johns Hopkins University Press, 2006)
"Through his insightful readings of dozens of classic and popular books for the young - from Beatrix Potter to Harry Potter, from Little Red Riding Hood to The Wind in the Willows to Goodnight Moon - noted scholar and columnist Jerry Griswold explores the unique qualities of childhood experience and the ways in which they reappear as frequent themes in children's literature. Great writers for children succeed, he demonstrates, because of their uncanny ability to remember and evoke the feeling of being a kid: hiding under tables, shivering in bed on a scary night, arranging miniature worlds of toys, flying around as caped superheroes, conversing with dolls over tea." --Book Jacket
Contents Introduction Chapter One. Snugness Chapter Two. Scariness Chapter Three. Smallness Chapter Four. Lightness Chapter Five. Aliveness Acknowledgments Bibliography Index
Includes bibliographical references (pages 129-138) and index
Keywords: Children's literature -- History and criticism; Children's literature -- Themes, motives